2021
DOI: 10.1038/s41398-021-01320-y
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Multimethod investigation of the neurobiological basis of ADHD symptomatology in children aged 9-10: baseline data from the ABCD study

Abstract: A Correction to this paper has been published: https://doi.org/10.1038/s41398-021-01320-y

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…the main covariables were balanced between the groups, even though it may increase the classification difficulty. Recently, Owens et al (2021) reported cross-validated elastic net regression to predict a continuous measure of ADHD symptomatology. Elastic net regression can simultaneously implement feature selection and regression by adding weighted L1/L2 regularized terms to the linear model's loss, limiting the scale of variable coefficients for avoiding overfitting.…”
Section: Figure 5 | (A)mentioning
confidence: 99%
“…the main covariables were balanced between the groups, even though it may increase the classification difficulty. Recently, Owens et al (2021) reported cross-validated elastic net regression to predict a continuous measure of ADHD symptomatology. Elastic net regression can simultaneously implement feature selection and regression by adding weighted L1/L2 regularized terms to the linear model's loss, limiting the scale of variable coefficients for avoiding overfitting.…”
Section: Figure 5 | (A)mentioning
confidence: 99%